Clinical outcomes and the role of adjuvant concurrent chemoradiation therapy in d2-resected ln-positive young patients (≤45 years) with gastric cancer - Yu, Jeong Il; Lim, Do Hoon; Lee, Jeeyun; Kang, Won Ki; Park, Se Hoon; Park, Joon Oh; Lim, Ho Yeong; Kim, Seung Tae; Kim, Sung; Sohn, Tae Sung; Lee, Jun Ho; An, Ji Yeong; et al. (Anticancer Research, 2019)
Background/Aim: This study aimed to investigate the clinical outcomes and role of adjuvant concurrent chemo-radiation therapy (CCRT) compared to adjuvant chemotherapy alone in young patients with gastric cancer (GC) defined as those ≤45 years old versus older patients. Patients and Methods: Data were collected from December 2004 to January 2013 on patients with pathologically confirmed, regional lymph node metastasis of GC who had undergone curative D2 resection. Results: During the study period, a total of 1,633 patients (341 young and 1,292 older GC) was investigated. Female sex and diffuse type were more frequent among the younger group, but, lymphatic and venous invasion were less frequent. During the follow-up, there was no difference in recurrence-free survival (RFS; p=0.81), but RFS was significantly higher in young patients with stage II GC (p=0.02). In the younger group, adjusted RFS did not differ according to adjuvant treatment (p=0.98), but the RFS was significantly higher in the older group treated with CCRT than with chemotherapy alone after adjustment for significant prognostic factors (p=0.008). Conclusion: Although young patients with GC had different characteristics, their clinical outcomes did not differ from those of the older patients. In the present study performed in curatively D2-resected GC, there was no benefit from adjuvant CCRT over chemotherapy alone among young patients, unlike among the older patients.
Keywords: Adult; Aged; Aged, 80 and over; Chemoradiotherapy; Chemotherapy, Adjuvant; Combined Modality Therapy; Disease-Free Survival; Female; Gastrectomy; Humans; Male; Middle Aged; Prognosis; Stomach Neoplasms; Gastric cancer; Patterns of failure; Radiotherapy; Recurrence; Young